Rachunkowość jako źródło informacji na potrzeby zarządzania ryzykiem przedsiębiorstwa - Nowak, Edward (Accounting as an Information Source for Company Risk Management Needs, 2008)
The paper discusses on information support for company risk management. The concept of company risk management inadequacy of practical solution has been depicted. The importance of accounting information in company risk management process was shown. Special attention has been given to the information about the risk which had been given in financial statements.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 96-104